2013
DOI: 10.1364/josab.30.002271
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic surface waves at a metal 2D photonic crystal interface

Abstract: The conditions to observe and excite electromagnetic surface modes at the interface between a two-dimensional (2D) photonic crystal (PC) and bulk metal are studied. It is shown that these modes can exist in the region where bandgaps of the PC overlap with the region below the plasma frequency of a metal in the dispersion diagram in both polarizations. The dispersion relation of these electromagnetic surface modes is determined numerically by considering a system of a thin metallic layer in contact with a finit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…The use of metallic films in contact with photonic crystals to produce PC-metal interface modes with two-dimensional photonic crystals has been discussed in great detail in [15].…”
Section: The Pcwg-pcmm Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of metallic films in contact with photonic crystals to produce PC-metal interface modes with two-dimensional photonic crystals has been discussed in great detail in [15].…”
Section: The Pcwg-pcmm Systemmentioning
confidence: 99%
“…Using the PCWG mode as a source, they found the total power of the waveguide mode is transferred completely to the surface mode and vice versa along a distance called the full transmission length. Very recently the interface modes between a metal and a 2DPC were studied [15] and it was found that, for an appropriate metal thickness and under resonant conditions, a large fraction of the incident light can be transferred to the interface wave.…”
Section: Introductionmentioning
confidence: 99%
“…As for the interface PhC-metal, the role of modes of the second type related to a forbidden band was stressed in [3]. As a rule, publications concerning SPP excitation in PhCs consider only the second-type evanescent waves (see, for example, [4][5][6]). Contrastingly, in our previous works we considered the first variant for SPP excitation ( [7]).…”
Section: Introductionmentioning
confidence: 99%
“…Using the PCWG mode as a source, the authors found that the total power of the waveguide mode is transferred completely to the surface mode and vice versa, along a distance called the full transmission length. Quite recently, the interface modes between a metal and 2DPC were studied and the authors found that for an appropriate metal thickness and under resonant conditions, a large fraction of the incident light energy can be transferred to the SW [33].…”
Section: Introductionmentioning
confidence: 99%